Development of a detector based on a CVD-diamond for the use in radiotherapy facilities - Akulinichev, S.V.; Klenov, V.S.; Kravchuk, L.V.; Lebedev, S.G.; Feschenko, A.V.; Yants, V.E. (Вопросы атомной науки и техники, 2006)
High radiation hardness, chemical resistance, high temperature operation capabilities stimulate a growing interest to use diamond materials as detectors of ionizing radiation. Samples of CVD-diamond materials in sizes 4×3 mm and 4×1 mm with thickness from 50 microns up to 500 microns have been grown in INR RAS using a DC glow discharge in a mixture of gases CH4/H2 on molybdenum substrates.